Self-assembled biomimetic architectures : protein-polymer conjugates and lipid-polymer hybrids for biomedical applications - Khan, Amit Kumar (Nanyang Technological University, 2018)
Macromolecular self-assembly is the foundation of all natural architecture starting from acellular virus particles to complex cellular constructs. In order to mimic such assemblies, we need to understand the fundamental aspects of selfassembly and the associated parameters governing the self-assembly at the nanometer to micrometer length scales. Self-assembly of single component macromolecular systems based on lipids, polymers and proteins have been studied extensively. However, the self-assembly behavior when they are combined is not well understood. Hence, the objective of this thesis is to design hybrid architectures (i.e., lipid-polymer and protein-polymer) and advance the understanding of their self-assembly behavior. For example, mixing phospholipids and polymers into hybrid self-assembled systems often give rise to bilayer thickness mismatch, which stems from differences in their chemical configurations and size. To overcome this mismatch and to have more energetically favorable system, low-molecular-weight biodegradable polymers and lipids are chosen to self-assemble into vesicles with bilayer thickness similar to that of a natural lipid bilayer membrane. From the experimental results, such hybrid configuration (although containing a high amount of polymer (50%)), possess lipid-like properties. For instance, they display an attenuated response to enzymatic digestion, reminiscent of PEGylated lipid vesicles. Notably, the lowmolecular- weight (< 4 kDa) biodegradable polymers alone form micelles. However, when mixed, the presence of phospholipid drives vesicular assembly for this type of hybrid polymer/lipid systems. For constructing hybrid vesicles, at the nano- and micron-scales, conventional methods such as film rehydration and electroformation methods were employed. To characterize the hybrid vesicles, dynamic light scattering, cryogenic transmission electron microscopy and calcein leakage experiments were performed. The experimental results reveal that such vesicles possess similar properties (size, bilayer thickness, and small molecule encapsulation capability) to vesicular membranes at the nanoscale. Furthermore, at the micro scale (i.e., micron size giant hybrid vesicles), their surface topologies were found ii to be homogeneous, independent of cholesterol, suggesting that these polymers possess a different polymer-lipid phase separating behavior as compared to the high molecular weight analogs. While exhibiting a similar bilayer thickness as that of lipid vesicles, functional differences in surface topology were demonstrated using the interfacially sensitive phospholipase A2. Biodegradable vesicles appear less sensitive to phospholipase digestion, reminiscent of PEGylated vesicles. Varying degrees of sensitivities towards phospholipase digestion were noticed implying that the nanoscale surface topology can further be tuned depending on the nature of the external ligands. This may be useful in designing vesicles for controlled release and supporting integral membrane protein in a semi-synthetic lipid-like environment. Besides, lipid-polymer self-assembled architecture, another class of giant amphiphile, protein-polymer conjugated assemblies is gaining much attention nowadays. Because of their structural complexity and functional diversity, they are regarded as potentially important candidates over conventional phospholipid and polymer-based assemblies. In Chapter 4, I describe the synthesis and characterization of a new protein-polymer conjugated vesicular architecture, proteinosome vehicle for biomedical -assemble by supercharging via amination or succinylation followed by conjugation with PEG. An equimolar mixture of the oppositely charged protein-polymer conjugates selfassemble into spherical capsules of 80-100 nm in diameter. A major advantage is that the described assembly process is performed entirely in aqueous solution without the need of a template. The self-assembly process is driven by the protein-polymer conjugates amphiphilicity and polyelectrolyte nature. Furthermore, the protein-polymer capsules or proteinosomes are reminiscent of viral protein capsids and are capable of encapsulating solutes in their interior. A better understanding of these systems might help employing them in future biomedical applications.